2004
DOI: 10.1021/la040058h
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Aliphatic Self-Assembled Monolayers by Free-Radical-Dominant Plasma:  The Role of the Plasma Composition

Abstract: Modification of octadecanethiolate self-assembled monolayers on Au by nitrogen-oxygen or argon-oxygen downstream microwave plasma with a low oxygen content (estimated below several percent) has been studied by synchrotron-based high-resolution X-ray photoelectron spectroscopy and water contact angle measurements. For both types of plasma, the primary processes were found to be the loss of conformational and orientational order and the oxidation of the alkyl matrix and headgroup-substrate interface. At the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 26 publications
(57 reference statements)
1
47
0
Order By: Relevance
“…The presence of TiO2 resulted from the presence of residual oxygen in the reactive chamber. In addition, minor oxygen species in the ionic or free radical state are recognized as highly reactive species, and the composition of reactive species in non-oxygen plasma may have an effect on the surface properties of a thin PIII-treated layer 25) . As for nitrogen, it is the most common atom in NiTi alloys and stainless steel to enhance their mechanical properties and corrosion resistance 26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of TiO2 resulted from the presence of residual oxygen in the reactive chamber. In addition, minor oxygen species in the ionic or free radical state are recognized as highly reactive species, and the composition of reactive species in non-oxygen plasma may have an effect on the surface properties of a thin PIII-treated layer 25) . As for nitrogen, it is the most common atom in NiTi alloys and stainless steel to enhance their mechanical properties and corrosion resistance 26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 1, the image of the topographical map taken in the semi-contact mode of a 10×10 μm 2 zone is shown. Figure 1 Most SAMs studies were established on the ideal, well-ordered and smooth single-crystal silicon (100 or 111) wafers primed with a metal adhesion layer (Weng et al, 2004(Weng et al, , 2006. On the single-crystal silicon wafers, theoretically, all alkanethiols should be bound onto the SAMs surface as an Au-S-C-structure.…”
Section: Atomic Force Microscopy Image Of Qcm Ship Surfacementioning
confidence: 99%
“…Presumably, only a small fraction of electrons and ionized species survives during the transport to the afterglow region. However, there is still a noticeable portion of long-living free radicals [6][7][8], which can become the dominant reactive species in the afterglow region.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have shown that low-density (∼ 10 6 particles/cm 3 ) downstream plasma can be successfully used to modify ultra-thin organic films, such as, e.g., aliphatic and aromatic thiol-derived selfassembled monolayers (SAMs) [1,2,7,8]. There are several major processes, which occur both simultaneously and subsequently during the exposure of SAMs to the plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation